Handbook of Biomaterial Properties - Murphy, William; Black, Jonathan; Hastings, Garth; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2016)
This book provides tabular and text data relating to normal and diseased tissue materials and materials used in medical devices. Comprehensive and practical for students, researchers, engineers, and practicing physicians who use implants, this book considers the materials aspects of both implantable materials and natural tissues and fluids. Examples of materials and topics covered include titanium, elastomers, degradable biomaterials, composites, scaffold materials for tissue engineering, dental implants, sterilization effects on material properties, metallic alloys, and much more. Each chapter author considers the intrinsic and interactive properties of biomaterials, as well as their appropriate applications and historical contexts. Now in an updated second edition, this book also contains two new chapters on the cornea and on vocal folds, as well as updated insights, data, and citations for several chapters.
From the Contents: Cortical bone -- Cancellous bone -- Dentine and enamel -- Cartilage -- Fibrocartilage -- Ligament, tendon and fascia -- Skin and muscle -- Brain tissues -- Arteries, veins and lymphatic vessels -- The intraocular lens -- Blood and related fluids -- The vitreous humour -- Properties of diseased musculoskeletal tissues -- Properties of diseased cardiovascular tissues -- Metallic biomaterials -- Stainless steels -- CoCr-based alloys -- Titanium and titanium alloys.
Keywords: Biomaterials; Biomedical engineering; Biophysics; Biomaterials; Biomedical Engineering and Bioengineering; Biophysics